2011
DOI: 10.1111/j.1439-0272.2010.01101.x
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in exons 5, 7 and 8 of the human voltage-dependent anion channel type 3 (VDAC3) gene in sperm with low motility

Abstract: Summary Voltage‐dependent anion channels (VDACs1‐3) are pore‐forming proteins located in the outer mitochondrial membrane of various tissues and in human sperm flagella. VDACs are involved in metabolite fluxes between mitochondria and other cell compartments and play a role in the motility of mammalian spermatozoa. VDAC3‐deficient male mice lacking exons 5–8 were reported to be healthy but infertile (Sampson et al., 2001). We analysed mutations in these exons of the human VDAC3 (hVDAC3) gene in spermatozoa of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
(37 reference statements)
0
5
0
1
Order By: Relevance
“…More recently, pathogenic variants affecting members of the SLC26 family of anion exchangers, namely SLC26A3 and SLC26A8 ( TAT1 ), were also shown to impair the functionality of the cystic fibrosis transmembrane conductance regulator (CFTR) channel, causing asthenozoospermia, associated with defective capacitation, midpiece and annulus disorganization in the case of SLC26A8 11,40,41 . The voltage‐dependent anion channels VDAC2 and 3 were also identified with pathogenic defects leading to idiopathic asthenozoospermia 9,42 . The specific location of all those ion channels/transporters at the plasma membrane of sperm cells, constitutes an interesting cellular background for potential therapeutic strategies to improve sperm motility in asthenozoospermic men.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, pathogenic variants affecting members of the SLC26 family of anion exchangers, namely SLC26A3 and SLC26A8 ( TAT1 ), were also shown to impair the functionality of the cystic fibrosis transmembrane conductance regulator (CFTR) channel, causing asthenozoospermia, associated with defective capacitation, midpiece and annulus disorganization in the case of SLC26A8 11,40,41 . The voltage‐dependent anion channels VDAC2 and 3 were also identified with pathogenic defects leading to idiopathic asthenozoospermia 9,42 . The specific location of all those ion channels/transporters at the plasma membrane of sperm cells, constitutes an interesting cellular background for potential therapeutic strategies to improve sperm motility in asthenozoospermic men.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, they have been intensively studied in mammalian spermatozoa. A first study reported several variants in the VDAC3 gene that distinguish asthenozoospermic patients from normozoospermic individuals [ 46 , 47 ]. These variants consist of deletions in exons 5 to 8 and missense mutations in exons 6 to 7 (Ile131Leu, Lys171Glu, Asp228Asn), which were not found in control individuals.…”
Section: Mutations In Ion Transporters and Channels That Results In H...mentioning
confidence: 99%
“…Protein VDAC diketahui berhubungan dengan berbagai proses biologis yang terjadi pada mitokondria seperti metabolisme energi dan apoptosis. 26,27,28 Penelitian dengan metode knock out gene VDAC3 pada ekson 5 -8 pada mencit menunjukan VDAC3 bersifat spesifik sperma dan mampu mempengaruhi motilitas sperma sehingga mencit jantan yang tidak memliliki fragmen gen tersebut menjadi infertil tanpa mengubah struktur testis dan jumlah sperma. 29 Berdasarkan uji hambatan antibodi antiVDAC3 terhadap sperma dapat diketahui bahwa antibodi VDAC3 murni dapat meningkatkan jumlah sperma yang tidak bergerak dan juga dapat menurunkan kecepatan pergerakan sperma normal.…”
Section: Puslitbang Sinergis Asa Professional Jemberunclassified